THE SCIENTIFIC RATIONALE FOR PLOUGHING TO INCREASE SOIL POROSITY - Sadullaev, Azamat Nafiddinovich; Jo‘rayeva, Shaxrizoda Imom qizi (Educational Research in Universal Sciences, 2024)
This scientific article delves into the fundamental principles and consequences of increasing soil porosity via tillage practices. By employing a comprehensive approach encompassing field experiments, soil analyses, and mathematical modeling, the study explores the intricate mechanisms behind enhanced soil porosity through various tillage methods. The investigation delves into the implications of altered porosity on water dynamics, nutrient availability, and overall soil health, providing valuable insights for optimizing agricultural practices. Explores the role of increased soil porosity in erosion control, evaluating how tillage practices contribute to maintaining soil structure and preventing soil loss. Examines changes in soil microbial communities resulting from altered porosity, investigating how tillage practices influence microbial activity and nutrient cycling.